Pengaruh Inovasi Produk dan Marketing Strategy Pada Produk Halal Paragon Terhadap Keputusan Pembelian Di Kalangan Mahasiswa - Kemal Rahardiansyah Putra; Afifudin Afifudin; Hariri Hariri (El-Aswaq: Islamic Economics and Finance Journal, 2022)
The purpose of this study was to determine the effect of product innovation and marketing strategy of Paragon's halal products on purchasing decisions. As for the method used in this study, namely the correlational quantitative method with several stages of research carried out by distributing questionnaires, data collection and data analysis. The data were tested using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, R2 determination test, and t test. The results of this study indicate that the product innovation variable has a positive and significant effect on purchasing decisions, while the marketing strategy variable has no significant effect on purchasing decisions